Indução de resistência, em bovinos, à intoxicação por plantas que contêm monofluoroacetato por meio da administração de análogo - Aristóteles Gomes Costa (2018)
Monofluoroacetate (MFA) is considered one of the most toxic substances known, and it is found naturally in plants responsible for causing sudden death syndrome in ruminants. Due to the hyperacute evolution of the poisoning and the impossibility of effective treatment, the induction of animal resistance might be the best tool to control MFA poisoning in ruminants. The objective of this study was to promote resistance in cattle to the toxic effects of MFA through its degradation by the ruminal microbiota after administration of sodium trifluoroacetate (TFA). Ten calves were used, distributed into two groups: control group (N=3) and treated group (N=7). The animals from the treated group received TFA, while those in the control group received water, both for 28 consecutive days. The animals were submitted to daily clinical evaluation and weekly blood biochemical determination, in order to identify any sign of poisoning. After 28 days of administration of TFA or water, application of the leaves of Palicourea marcgravii was performed to determine the occurrence of resistance. The administration of TFA was not responsible for any clinical or biochemical changes in blood. The administration of P. marcgravii induced clinical changes in the control group of cattle, but no alteration was observed in the animals of the treated group. Thus, the administration of TFA to cattle induces resistance to MFA poisoning.